THE EFFECT OF ENGLISH AS AN OPTIONAL SUBJECT AT ELEMENTARY SCHOOL TOWARDS JUNIOR HIGH SCHOOL ENGLISH PRODUCTIVE SKILL (A Study at SMPN 26 Kota Serang) - Rachmatia; Nurhaeda Gailela (BEGIBUNG: Jurnal Penelitian Multidisiplin, 2025)
English is an optional subject in elementary school, but it has many cons. Of this problem, the researcher wanted to seek out the effect of English as an optional subject in elementary school on junior high school English productive skill. The researcher used a mixed method with the ex-post facto design, where quantitative data were processed before qualitative data. Questionnaires, interviews, and open-ended tests were used to gain the data. All the data analyses were counted on SPSS. The respondents were 45 students at SMPN 26 Kota Serang with criteria for 7th-grade JHS students who previously had English as an optional subject. The results showed negative and non-significant simultaneous effects between learning English as an optional subject at Elementary school towards Junior High School students’ English productive skills with an f-value of 0.154 with a significance value of 0.858 (far above 0.05). The students struggled to improve their speaking and writing skills in junior high school due to the lack of active practice opportunities. This results in a lack of foundational English—skills, and difficulty meeting higher standards at Junior High School.